2001
DOI: 10.1111/j.1530-0277.2001.tb02151.x
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Use and Sexual Risk Taking Among Hazardously Drinking Drug Injectors Who Attend Needle Exchange

Abstract: Alcohol use is associated with sex risk-taking behavior among injection drug users. A substantial majority of participants reported using alcohol before or during sexual relations, which temporally links alcohol use with human immunodeficiency virus injection risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
1
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 47 publications
3
24
1
3
Order By: Relevance
“…These findings suggest that at least some recent club drug users are in need of treatment or counseling for both drug use and other psychosocial problems, which may include sexual or physical abuse, delinquency or criminality, school problems, psychological distress, and family dysfunction (e.g., poor parenting or family substance use) (e.g., Chilcoat and Anthony, 1996;Galaif and Newcomb, 1999;Johnson and Leff, 1999;Martin et al, 1996;Moran et al, 2004). Further, the clustering of drug use and alcohol abuse or dependence is a cause for concern because of its heightened risk for HIV-related risky behaviors and consequences (Baldwin et al, 2000;Rasch et al, 2000;Stein et al, 2000Stein et al, , 2001. Hence, prevention or treatment programs should include risk-reduction interventions to increase club drug users' knowledge of HIV prevention and to reduce unprotected sexual behaviors (Semple et al, 2004;Yen, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that at least some recent club drug users are in need of treatment or counseling for both drug use and other psychosocial problems, which may include sexual or physical abuse, delinquency or criminality, school problems, psychological distress, and family dysfunction (e.g., poor parenting or family substance use) (e.g., Chilcoat and Anthony, 1996;Galaif and Newcomb, 1999;Johnson and Leff, 1999;Martin et al, 1996;Moran et al, 2004). Further, the clustering of drug use and alcohol abuse or dependence is a cause for concern because of its heightened risk for HIV-related risky behaviors and consequences (Baldwin et al, 2000;Rasch et al, 2000;Stein et al, 2000Stein et al, , 2001. Hence, prevention or treatment programs should include risk-reduction interventions to increase club drug users' knowledge of HIV prevention and to reduce unprotected sexual behaviors (Semple et al, 2004;Yen, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This reliable method has been used extensively in substance use research 82 and specifically with adolescents for recall of both substance use 83 and sexual behavior. 83,84 The timeline followback calendar uses recall-enhancing techniques to provide a detailed assessment of substance use and coitus at the event level.…”
Section: Retrospective Reportmentioning
confidence: 99%
“…This reliable method has been used extensively in substance use research 82 and specifically with adolescents for recall of both substance use 83 and sexual behavior. 83,84 The timeline followback calendar uses recall-enhancing techniques to provide a detailed assessment of substance use and coitus at the event level.Because it would have been difficult to recall the specifics of affect on any given day, participants were asked to give a general impression of their affect for each of the 14 days, noting in particular days with the best and the worst affective states. The interview took ϳ30 minutes (more or less, depending on the frequency of substance use and sexual behavior).…”
mentioning
confidence: 99%
“…The HIV + IDUs are more likely to disclose their HIV serostatus to primary partners than to other partners (9). Numerous studies have found that condom use is more likely with IDUs' nonsteady partners than with primary or steady partners (1,5,6,(8)(9)(10)(11)(12)(13). Additional sexual risk behaviors practiced by IDUs involve exchanging sex for drugs or money, engaging in sexual intercourse with other IDUs, and using alcohol and/or drugs prior to or during sex (8,(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%